2018
DOI: 10.18778/0208-6018.334.07
|View full text |Cite
|
Sign up to set email alerts
|

M‑communication in Product Information Exchange – an International Comparison

Abstract: The main objective of the paper is to identify the degree to which Social Networking Sites (SNSs) are used in communication related to gathering information about products via mobile devices (mobile communication). The research problem is presented in the context of Computer Mediated Communication theory (CMC). In the realisation of the main purpose of this paper, an attempt has been made to answer two research questions: firstly, is there a relationship between types of products and the frequency of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Under these conditions, consumers are unwilling to accept higher product prices [37]. In addition, Polish culture is individualistic, which further favors green skepticism [18,44].…”
Section: Skepticism About the Social Responsibility Of Entrepreneurs ...mentioning
confidence: 99%
“…Under these conditions, consumers are unwilling to accept higher product prices [37]. In addition, Polish culture is individualistic, which further favors green skepticism [18,44].…”
Section: Skepticism About the Social Responsibility Of Entrepreneurs ...mentioning
confidence: 99%
“…Despite the above, Hook et al (2008, 2012) noted that forgiveness in collectivist cultures may be more decisional than emotional forgiveness, so REACH interventions may serve different functions in different cultures. However, it should be noted that comparative studies have consistently indicated the individualistic nature of Polish and US societies (Bartosik‐Purgat & Schroeder, 2007), so there is no need to adapt the content of REACH Forgiveness to specific cultural conditions. Moreover, in our study, Polish participants reported similar emotional forgiveness scores compared to American students (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…According to (Gruen, 2006: 6) agreed that "Electronic word of mouth is to spread information about products and services that have been consumed between consumers who do not know each other and have never met. Research has shown how traditional word of mouth (WOM) and electronic word of mouth (e-WOM) influence consumer behavior and purchasing decisions (Bartosik-Purgat, 2018;Badir and Andjarwati, 2020;Kajtazi and Zeqiri, 2020). E WOM and WOM as business promotion tools play an important role, especially in the tourism industry.…”
Section: E-wommentioning
confidence: 99%